2005
DOI: 10.1074/jbc.m411894200
|View full text |Cite
|
Sign up to set email alerts
|

Mirk/dyrk1B Decreases the Nuclear Accumulation of Class II Histone Deacetylases during Skeletal Muscle Differentiation

Abstract: The availability of in vitro culture systems that recapitulate the major features of muscle cell differentiation has allowed much progress toward the elucidation of the molecular basis for muscle maturation and regeneration. An improved understanding of these processes might have significant clinical ramifications, such as the development of strategies to ameliorate damage to skeletal or cardiac muscle. A novel gene cloned in our laboratory (1, 2), the kinase Mirk, has the unusual properties of mediating cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 34 publications
3
80
0
1
Order By: Relevance
“…Moreover, expression of CaMKIV in HEK293 cells promoted export of HDAC5 but had minimal effects on Ser-279 phosphorylation (data not shown). Mirk/ dyrk1B was shown to phosphorylate Ser-243 of an alternatively spliced isoform corresponding to the N-terminal half of HDAC9 (78). However, expression of this and related kinases did not alter the subcellular localization of class IIa HDACs in our assay conditions (data not shown).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, expression of CaMKIV in HEK293 cells promoted export of HDAC5 but had minimal effects on Ser-279 phosphorylation (data not shown). Mirk/ dyrk1B was shown to phosphorylate Ser-243 of an alternatively spliced isoform corresponding to the N-terminal half of HDAC9 (78). However, expression of this and related kinases did not alter the subcellular localization of class IIa HDACs in our assay conditions (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…Additional phosphorylation sites have been identified in class IIa HDACs, including Ser-298 of HDAC4 (36), Ser-253 of the HDAC9 splice variant (78,82), and multiple residues of HDAC4 and HDAC5 reported by phosphoproteomic studies (see the Human Protein Reference Database) (79,80,83,84), suggesting that complex multisite phosphorylation programs may respond to cAMP and other upstream signaling cues (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…Dyrk1B phosphorylates HDAC5 at a serine residue shared by HDAC4 and HDAC9, but not by HDAC7. Phosphorylation by Dyrk1 reduces their nuclear accumulation and leads to MEF2 activation (Deng et al, 2005). This residue does not correspond to a 14-3-3 binding site and its mutation does not prevent CaMK-induced nuclear export , but it lies within the nuclear localization region of class IIa HDACs.…”
Section: Other Posttranslational Modificationsmentioning
confidence: 99%
“…Depletion of endogenous Mirk by RNA interference blocked the transcription of myogenin and the subsequent myoblast differentiation program (1). Mirk controls the activation of the myogenin transcription factor MEF2 by regulating nuclear accumulation of the MEF2 inhibitors, class II histone deacetylases (2). However, it has been reported that embryonic knockout of Mirk did not block skeletal muscle development in the early embryo (3), suggesting that Mirk may have a more significant function in muscle repair than in initial myogenesis.…”
mentioning
confidence: 98%
“…Mirk has also been shown to act as a transcriptional activator (2,12,13) and to inhibit cell motility (14). Because of these actions of Mirk on cell cycle regulators active in G 0 /G 1 during myoblast differentiation, we extended our study of Mirk substrates to p21 Cip1 .…”
mentioning
confidence: 99%